Strategi Pengembangan Objek Wisata Danau Mesjid Sebagai Objek Wisata Unggulan di Kabupaten Kuantan Singingi - Yuliarti, Rini (Jurnal Daya Saing, 2015)
Abstract: Koto Mesjid Lake Kari potential as a tourist attraction is very large. Then there is still the need for a strategy that can really be to develop a tourist attraction that is better known by the public. The method used is a method desktriptif. Results showed that the Office of Tourism Youth and Sports Kuantan Singingi as business work has made strides in developing Attractions Lake Mosque. They tried to run strategies are considered able to develop attractions Lake Mosque. Strategies undertaken by the Department of Tourism Youth and Sports such as: Boosting promotional activities, Doing Making regulation About Tourism Kuantan Singingi, Facilities Development and Infrastructure, Building Supporting Facilities, Attractions Lake Mosque Koto Kari has the potential object of sufficient good of the means as well as supporting infrastructure. This potential is supported by natural circumstances. Keywords: Strategy, Development attractions